2019
DOI: 10.1101/2019.12.11.872861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human NMD ensues independently of stable ribosome stalling

Abstract: Nonsense-mediated mRNA decay (NMD) is a translation-dependent RNA degradation pathwaythat is important for the elimination of faulty and the regulation of normal mRNAs. The molecular details of the early steps in NMD are not fully understood but previous work suggests that NMD activation occurs as a consequence of ribosome stalling at the termination codon (TC). To test this hypothesis, we established an in vitro translation-coupled toeprinting assay based on lysates from human cells that allows monitoring of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…3΄UTR construct as described before 15 . Amplification of the vector using the primers 5΄-AAT AAG AGC TCC TGC CTC GAG CTT CCT CATC-3΄ and 5΄-AAT AAC ATA TGG TGA TGC TAT TGC TTT ATT TGT AAC-3΄ was followed by restriction digestion with SacI and NdeI and ligation with a 6xMS2-containing insert that was PCR-amplified using the primers 5΄-AAT AAC ATA TGG TTC CCT AAG TCC AAC TAC CAA A-3΄ and 5΄-AAT AAA GAG CTC CCA GAG GTT GAT TGT CGA CC-3΄…”
Section: Preparation Of Viral 5'-utr Mrna and Reporter Rluc Mrnamentioning
confidence: 99%
See 3 more Smart Citations
“…3΄UTR construct as described before 15 . Amplification of the vector using the primers 5΄-AAT AAG AGC TCC TGC CTC GAG CTT CCT CATC-3΄ and 5΄-AAT AAC ATA TGG TGA TGC TAT TGC TTT ATT TGT AAC-3΄ was followed by restriction digestion with SacI and NdeI and ligation with a 6xMS2-containing insert that was PCR-amplified using the primers 5΄-AAT AAC ATA TGG TTC CCT AAG TCC AAC TAC CAA A-3΄ and 5΄-AAT AAA GAG CTC CCA GAG GTT GAT TGT CGA CC-3΄…”
Section: Preparation Of Viral 5'-utr Mrna and Reporter Rluc Mrnamentioning
confidence: 99%
“…Preparation of in vitro transcribed mRNAs was performed as described 15 Capping buffer (New England Biolabs). The capping reaction was carried out at 37 °C for 1 h and quenched by the addition of acidic P.C.I., followed by RNA purification.…”
Section: In Vitro Transcription Of Reporter Mrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies seemed to confirm the idea of slow and inefficient translation termination and ribosome recycling at PTCs due to the absence of a termination promoting 3′UTR mRNP structure that probably includes PABP [ 39 , 41 , 44 , 70 , 71 , 134 , 142 ]. However, according to a recent report, in vitro translation of reporter mRNAs followed by toeprinting in human cell lysates failed to detect a difference in ribosomal occupancy at the termination codons of reporter mRNAs with or without NMD-inducing 3′UTRs and with or without a Poly(A) tail [ 143 ]. These findings were corroborated by ribosomal profiling of endogenous NMD-sensitive and insensitive transcripts in HeLa cells, which revealed that ribosome occupancy at termination codons is similar in both types of transcripts.…”
Section: Is Termination At a Ptc Really Slower Than At An Ntc?mentioning
confidence: 99%